THE EFFECT OF TALENT MANAGEMENT PRACTICES, ORGANIZATIONAL SUPPORT, AND DISTRIBUTIVE JUSTICE ON EMPLOYEE TURNOVER INTENTION IN THE KUPVA BB SECTOR - Firo Enzo; Muhammad Donal Mon (Universitas Sarjanawiyata Tamansiswa, 2026)
The purpose of this study was to determine the influence of Talent Management Practices (TMP) on Employee Turnover Intention (TOI) in the KUPVA BB (Non-Bank Foreign Exchange Business Activities) sector in Batam city, while also determine the mediating roles of Perceived Organizational Support (POS) and Perceived Distributive Justice (PDJ). A quantitative approach by collecting data from 234 respondents who working in money changer businesses through an online questionnaire, was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via Smart-PLS 4.0. The results indicated that Talent Management Practices (TMP) significantly reduced Turnover Intention (TOI) both directly and indirectly through Perceived Organizational Support (POS) and Perceived Distributive Justice (PDJ) as mediators. These findings underscore the importance of implementing fair Talent Management Practices (TMP) and organizational support in retaining high-performing employees in a competitive business environment.